Tribological Behavior and Mechanical Properties of Graphene/PEEK Composites - Morris, J.; Ríos, R.; Castro, M.; Puértolas, J.A. (Jornada de Jóvenes Investigadores del I3A, 2017)
PEEK has been implemented in various orthopaedic applications due to its many beneficial mechanical, tribological, and radiolucent properties. These properties can be further tailored by introducing fillers into the PEEK matrix. In this work, graphene has been incorporated due to its high mechanical resistance, intrinsic stiffness, and lubricating properties [2].